Preparation and Characterization of Graphene Oxide Reduced From a Mild Chemical Method - Oh, Won-Chun; Zhang, Feng-Jun (Asian Journal of Chemistry, 2010)
Layer structured graphene oxide (GO) was prepared from graphite using the modified Hummers- Offeman method. These layers were comprehensively characterized by X-ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscopy, energy dispersive X-ray analysis, transmission electron microscopy, Raman spectroscopy and atomic force microscopy. FT-IR and EDX measurements indicate the formation of layered structure with strong functional groups of graphene oxide and small partial oxygen containing functional groups were still existed in the sample of reduction of graphene oxide (RGO). From the TEM images, monolayer graphene oxide could be found in a flake form in the graphene oxide and reduction of graphene oxide layers. The intensity ratio between D peak and G peak in the Raman spectra of graphene oxide and reduction of graphene oxide indicated that the as-prepared graphene oxide has a low defect content. Atomic force microscopy results showed that the single layer of graphene oxide has been produced.